Responding to a measles outbreak in a Pacific Island community in western Sydney: community interviews led to church-based immunization clinics - Scott, Nicola; Gabriel, Salwa; Sheppeard, Vicky; Peacock, Alisa; Scott, Caroline; Flego, Kristina; Forssman, Bradley; Seale, Holly (Western Pacific Surveillance and Response, 2015)
Introduction: There are large Pacific Island (PI) communities in western and south-western Sydney, New South Wales (NSW), Australia. In 2011 and 2012, measles outbreaks disproportionally affected children and youth within these communities. The objectives of the study were to explore barriers to immunisation in the PI community from the perspectives of community members and health professionals and to conduct a pilot program whereby immunisation catch-up clinics were held in a Samoan church in western Sydney.Methods: Interviews were conducted with PI community members (n=12) and health professionals connected with the PI community (n=7) in 2013. Interviews were transcribed and analysed thematically. A partnership with a local Samoan church was established to provide an accessible venue for community members to attend the immunisation catch-up clinics.Results: Amongst the community members there were high levels of belief in the importance of immunisation and a positive view regarding the ‘protection’ offered by immunisation. A key barrier identified was being busy and therefore having limited time to get children immunised. The important role of the church within the community was emphasised in the interviews and as a result two immunisation catch-up clinics were held in a Samoan church in western Sydney. The age range of attendees was 7-33 years old, a total of 31 measles mumps rubella (MMR) doses and 19 meningococcal C doses were given over the two clinics.Discussion: The outcomes of the interviews and the subsequent clinics highlight the potential of church as a venue for providing public health interventions such as catch-up immunisation.